MAKNA IMPLISIT "PEDANG” DALAM KANJI BER-BUSHU RITTO - Khusnaini, Milatul; Hadiutomo, Dwi Anggoro (Japanology: The Journal of Japanese Studies, 2023)
Bushu are the basic elements in Japanese Kanji that make up the meaning of the letters. However, there are kanji letters that are not always directly related to the meaning of the bushu it has. This article aims to describe bushu ritto (刂) which means 'sword' and the kanji characters that contain the bushu element, but do not have a direct meaning of 'sword'. The eight kanji characters studied are 列 /retsu, 制 /sei, 剛 /gou, 到 /tou, 前 /zen, 割 /katsu, 副 /fuku, and 則 /soku. The theory used in the analysis is the theory of the origin of the kanji rikusho. The results of the analysis show that all kanji characters using bushu ritto (刂) do not always have a meaning directly related to 'sword.' However, further analysis shows that these letters still have connotative or associative meanings related to 'sword' or related activities, such as 'cutting' or 'sorting'. The kanji 列 /retsu, 剛 /gou, and 副 /fuku can be physically associated with the concept of 'sword', while the kanji 制 /sei, 到 /tou, 前 /zen, 割 /katsu, and 刷 /satsu can be associated with actions that involve the use of a 'sword,' such as 'cutting,' 'scraping,' and 'sorting.'